2010
DOI: 10.3928/00220124-20100423-09
|View full text |Cite
|
Sign up to set email alerts
|

Twitter: Consider the Possibilities for Continuing Nursing Education

Abstract: Staying connected virtually has become a mainstay of modern American culture. Twitter has become the "front porch" of the 21st century. This column explores this growing social media tool and its use in health care and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 2 publications
0
25
0
3
Order By: Relevance
“…The most used instruments among teachers from both types of schools, although with different percentages, were blogs, wikis, video casts and podcasts. Bristol (2010) states that staying connected virtually is now a mainstay of modern culture. According to Skiba [26], information is not only transmitted but is also exchanged, new knowledge is generated, interaction between people is continuous and new relationship networks are built.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most used instruments among teachers from both types of schools, although with different percentages, were blogs, wikis, video casts and podcasts. Bristol (2010) states that staying connected virtually is now a mainstay of modern culture. According to Skiba [26], information is not only transmitted but is also exchanged, new knowledge is generated, interaction between people is continuous and new relationship networks are built.…”
Section: Resultsmentioning
confidence: 99%
“…The use of social media as a training tool in nursing education is recommended to support clinical learning, communication, connection, exchange and partnerships [22][23][24][26][27][28][31][32][33]. Some authors have already evaluated and demonstrated this [25,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alle studentene hadde tilgang til epostadresser via den digitale laereplattformen, men analyser av studentenes utbytte av mailutvekslingen inngår ikke i denne studien. Nettbaserte samarbeid kan innebaere at studentene bruker e-post og epostlister som verktøy (21), og nye sosiale medier som twitter og facebook (22).…”
Section: Aktiviteten På Digital Laereplattformunclassified